OPTIMIZING FIXATION DURATION FOR ENHANCED CLARITY IN Pediculus humanus-capitis WHOLE MOUNT PREPARATIONS USING 10% KOH AT 70°C - Tika putri agustina; Musma Rukmana; Hasmiati; Fernando Andre Watung (LPPM Universitas PGRI Semarang, 2024)
This study evaluates the optimal fixation duration using 10% potassium hydroxide (KOH) at 70°C for whole mount preparations of Pediculus humanus capitis (head lice). Accurate head lice identification is crucial for effective public health management. Specimens were fixed for 20, 25, 30, 35, and 40 minutes at 70°C, then processed through rinsing, acetic acid treatment, dehydration, and clearing before mounting for microscopic examination. Results showed that 25 minutes of fixation provided the clearest and most detailed preparations. This duration effectively achieved tissue dehydration and clarification without significant damage. Fixation for 20 minutes was insufficient, resulting in opaque specimens due to incomplete KOH diffusion. Conversely, 40 minutes of fixation caused over-fixation, leading to tissue damage and poorer color quality. The study underscores the importance of finding the right fixation duration. While shorter times are inadequate, longer durations can degrade specimen quality. A 25-minute fixation at 70°C is optimal for balancing clarity and structural preservation, improving head lice identification. This method enhances the quality of whole mount preparations and provides practical guidance for accurate and reliable ectoparasite examination in clinical and research settings.